SISTEM INFORMASI PELAYANAN PASIEN RAWAT JALAN PADA PUSKESMAS PETIR MENGGUNAKAN METODE AGILE - Yul Hendra; Irma Yunita; Achmad Rifai; Andi Usri Usman (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
Puskesmas petir is one of the community health service centers located on Jl Tunjung-Petir Km. 17, District. Lightning Strike. Outpatient data processing at Lightning Health Center is a very important component to improve the quality of service to the community in the health sector. The Community Health Center feels the importance of information technology facilities, especially in processing patient data and making reports, which previously required more time and processing. One information system that is an alternative for hospitals in obtaining the necessary information is the Outpatient patient data processing information system. So far, data processing for registration, diagnosis, drug prescriptions, pharmacists and laboratories has not been integrated so that the data processing process is not yet optimal. There are many obstacles experienced by community health centers, including errors in inputting, storing data, taking a long time to search for patient data, and patient records being duplicated, so that data management becomes less effective and efficient. This can hinder the flow of reports and smooth service to patients. The development of this information system uses the Waterfall method. The results that will be achieved or expected from this research are that this information system can help the Lightning Health Center in managing outpatient data and speeding up the service process